Brief incubation of corneal grafts in activated platelet rich plasma enhances corneal endothelial cell survival and regeneration. (July 2022) - Gomez, Angela; Mercado, Carolina; Venkateswaran, Nandini; Sen-Corcuera, Borja de la; Miller, Darlene; Dubovy, Sander; Salero, Enrique; Sabater, Alfonso L.
Abstract: Corneal transplantation is the most frequent organ transplantation worldwide. Unfortunately, corneal graft failure is common and endothelial decompensation is considered the major cause. Corneal endothelial cells (CECs) lack the capacity to reproduce, and perioperative and postoperative endothelial cell loss remains a significant challenge associated with corneal graft viability. Therefore, strategies to preserve CEC density are critical to extend graft survival. Activated platelet rich plasma (aPRP), a product extracted from autologous blood, has both antioxidant and regenerative properties. aPRP eye drops have shown effectiveness in the treatment of corneal pathologies such as ulcers, dry eye, and burns. Our purpose is to determine the protective and regenerative effect of aPRP on corneal grafts by evaluating aPRP's effect on the survival and proliferation of human CECs. Human corneal grafts were incubated in aPRP for 15 min to assess the activation of the CEC pAkt survival pathway as measured by ELISA. Evaluation of the protective effect of aPRP was made using an apoptotic model, which simulated oxidative stress conditions. Expression of apoptotic markers was measured using ELISA and endothelial cell viability was determined by optical microscopy. The CEC proliferation rate was measured in vitro with Ki-67 staining. Corneal graft gross structure was evaluated by Hematoxylin & Eosin and Masson trichrome staining. Our results indicate that a short incubation of human corneal grafts in aPRP protects CECs from apoptosis by upregulating the pAkt survival pathway and promoting CEC proliferation. Additionally, aPRP incubation does not induce histological changes in the grafts. A brief pre-treatment of human corneal grafts in aPRP may be beneficial for transplant longevity, as it protects CECs from apoptosis by upregulating intracellular survival pathways and promoting proliferation. In addition, this approach appears to be safe and has the potential to improve surgical outcomes following corneal transplantation. Highlights: A short incubation of corneal grafts in aPRP protects corneal endothelial cells from apoptosis by upregulating Akt pathway. A short incubation of human corneal grafts in aPRP promotes corneal endothelial cell proliferation. A short incubation of human corneal grafts in aPRP does not induce histological changes in the grafts.